Rethinking Participatory Culture through the Case in Mulyana’s “Sea Remembers” - Wan Ridwan Husen; Budi Irawanto; GR Lono Lastoro Simatupang (International Journal of Business, Economics, and Social Development, 2025)
This study discusses the production process carried out in collaboration with the community (especially women's knitting groups) in the field of visual arts, seen through the lens of participatory culture. Using a case study approach, this study re-examines how artists engage with communities to create spaces for communication, build relationships, explore creative processes, exchange ideas, and collectively shape identities. This study examines the collaborative methods applied in Mulyana's artwork 'Sea Remembers', focusing on two main aspects: the collaborative work process and the community empowerment process. The method used is qualitative with a case study approach to a collaborative process. The findings reveal that during its production, 'Sea Remembers' illustrates that the artistic process carried out with many people can be a medium for empowering communities, can positively foster innovation in art making, and increase appreciation for those involved. This study emphasizes the potential of collaboration with a participatory approach in redefining the artistic production process in building social relationships.